POLA INTERAKSI KIAI DAN SANTRI SEBAGAI MODEL PEMBELAJARAN DI PONDOK PESANTREN MANBA’UL CHIKMAH SAPURAN WONOSOBO - Uminingsih, Ulfah; Shidiq, Ngarifin; Kamal, Faisal (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2025)
This study aims to determine how the influence of PTMT policy on the implementation of the revised 2013 curriculum and how the influence of PTMT policy on the implementation of the revised 2013 curriculum on teacher performance at MI Ma'arif in Mojotengah District. This study uses a quantitative approach, using a survey design. Data collection methods used include: questionnaire method, and documentation method. The research sample used a total sample of 60 teachers in MI Ma'arif, Mojotengah District, then the data collected was analyzed by simple linear regression. The results showed that: PTMT Policy on Curriculum Implementation the average total score of respondents' answers was 34. The mean of all total scores was 34. The lowest total score was 24, the highest score was 45. and the standard deviation was 4.2. While the level of teacher performance the average total score of respondents' answers to the questionnaire is 43. The middle score is 44. The lowest score is 17, the highest score is 52 and the standard deviation is 6.3. This study can be concluded that the PTMT Policy in the Implementation of the 2013 Revised Curriculum has a positive and significant effect on Teacher Performance This is shown from the test results, namely the comparison of t count is greater than t table, then Ho is rejected.